GST complexities in Malaysia: views from tax experts - Nutman, Naailah; Mohd. Isa, Khadijah; Yussof, Salwa Hana (Emerald Publishing Limited, 2022)
Purpose – The Goods and Services Tax (GST) implementation in Malaysia had raised various responses from many parties involved when the new tax was introduced in 2015 until its abolishment in 2018. GST complexity has been stated as part of the reasons for its resistance and abolishment. The purpose of this paper is to identify causes of GST complexities during its implementation in Malaysia.